Endocan - a potential diagnostic marker for early onset sepsis in neonates - Gabriela Ildiko Zonda; Radu Zonda; Andrei Tudor Cernomaz; Luminita Paduraru; Andreea Luciana Avasiloaiei; Bogdan Dragos Grigoriu (Journal of Infection in Developing Countries)
Introduction: Neonatal early onset sepsis assessment is based on the history of pregnancy and delivery and nonspecific clinical signs. None of the biomarkers currently in use for clinical practice has adequate prognostic value, so it is not possible to clearly distinguish neonates with culture-proven sepsis from those with only risk factors or clinical suspicion. Endocan is an endothelial mediator involved in the inflammatory response that is present in low concentrations in the serum of healthy subjects, and in much higher concentrations in patients with SIRS and septic shock. The purpose of this study is to evaluate the utility of serum endocan serum levels as a biomarker for the diagnosis of neonatal early onset sepsis (EOS).